2016
DOI: 10.1089/ars.2015.6415
|View full text |Cite
|
Sign up to set email alerts
|

Imaging Reactive Oxygen Species-Induced Modifications in Living Systems

Abstract: Significance: Reactive Oxygen Species (ROS) may regulate signaling, ion channels, transcription factors, and biosynthetic processes. ROS-related diseases can be due to either a shortage or an excess of ROS. Recent Advances: Since the biological activity of ROS depends on not only concentration but also spatiotemporal distribution, real-time imaging of ROS, possibly in vivo, has become a need for scientists, with potential for clinical translation. New imaging techniques as well as new contrast agents in clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
45
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(45 citation statements)
references
References 152 publications
(200 reference statements)
0
45
0
Order By: Relevance
“…It has also been reported that two α‐Toc• form poorly reactive non‐radical dimers (Fig. (15)) . The lipid peroxidation reaction introduced above can be expressed as a rate constant ( k ) using a two‐compartment kinetic model equation (Fig.…”
Section: Introductionmentioning
confidence: 95%
“…It has also been reported that two α‐Toc• form poorly reactive non‐radical dimers (Fig. (15)) . The lipid peroxidation reaction introduced above can be expressed as a rate constant ( k ) using a two‐compartment kinetic model equation (Fig.…”
Section: Introductionmentioning
confidence: 95%
“…Since only the radical form is characterized by EPR/MRI contrast, this could be used as a quantitative marker for the as-sessment of the redox status in biological objects in vitro and in vivo (91). Many excellent review articles have described this possibility (92,(95)(96)(97)(98).…”
Section: Nitroxides As Redox Sensors For Detection Of Mitochondrial Dmentioning
confidence: 99%
“…much more sensitive electrochemical detection of the DHE products) or new DHE analogs allowing sitespecific detection of superoxide (e.g. mito-SOX for mitochondrial superoxide and hydropropidine for extracellular superoxide) or the most advanced new spin traps providing higher stability in biological samples and thereby allow the EPR-based detection of superoxide and/ or peroxynitrite-derived free radicals in cells and tissues (some candidates might be found in [32,[135][136][137]). High performance liquid chromatography (HPLC)-based detection of superoxide formation in the extracellular space, cytosol and mitochondria can be established by hydropropidine, a positively-charged water-soluble analogue of dihydroethidium (DHE) for extracellular superoxide formation [138], DHE for cytosolic superoxide formation and mitoSOX, a mitochondria-targeted DHE analogue for mitochondrial superoxide formation (Fig.…”
Section: No the Reaction Ofmentioning
confidence: 99%
“…Combined with the respective spin trap, these techniques have the potential for the specific detection of vascular ROS and RNS formation in isolated tissues and whole animals [135,154]. Also combination of different techniques such as immuno-spin trapping as reported for trapping of thiyl radical in proteins or other radicals in DNA by DMPO and formation of stable spin-adducts with subsequent Western blotting against DMPO-bound proteins or DNA molecules are already used for the detection of ROS and RNS formation, or more precisely their footprints in biological samples [155].…”
Section: No the Reaction Ofmentioning
confidence: 99%
See 1 more Smart Citation